Evaluating the Usability of a Coconut Export Website Using the System Usability Scale (SUS) - I Ketut Ari Sadhu Gunawan; Renny Sari Dewi (Universitas Malikussaleh, 2026)
This study aims to evaluate the usability level of the PT Palm Trade Company website in order to improve user experience and system effectiveness. The method used is the System Usability Scale (SUS) as a standardized approach to assess users' perceptions of the ease of system use. Data were collected through the distribution of questionnaires to respondents who had directly interacted with the website. The obtained data were analyzed to generate usability scores and to evaluate various levels of user satisfaction. The results of the study indicate that the website falls into the acceptable category, suggesting that the system is generally easy to use and capable of meeting user expectations. However, there are aspects that require further improvement, particularly in terms of interface design and navigation efficiency. The analysis of the coconut export website generally meets usability standards, but requires ongoing improvements to enhance the user experience and support the effectiveness of export transactions. Recommendations for improvement are expected to serve as a guide for developers in optimizing the quality of digital services. In addition, several issues were identified related to information consistency and visual appearance. Based on these findings, several recommendations are proposed to enhance the overall quality and performance of the website. This study concludes that usability evaluation plays an important role in supporting digital platforms, especially in complex agribusiness companies.